Militarising school: militarism in the Turkish educational system (1926-1947) - Gunduz, Mustafa (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2018)
With the advent of modern states, a mandatory relationship and interaction emerged between compulsory education, military service, and the practices of citizenship. Producing a loyal citizen required a disciplined, central, and compulsory education. In the nineteenth century when greatness was linked to armament, education was considered a vital aspect of social and military mobilisation. For this reason, rituals and practices in favour of military service were included in many education programmes. New applications were introduced and military themes integrated into courses such as physical education, gymnastics, history, and geography. Similar initiatives were seen in the Ottoman Empire in the second half of the nineteenth century. Thereafter, military education and paramilitary organisations which became popular during the First World War gained another dimension in the republican period that followed the collapse of the empire. Military service preparation was made a compulsory course at every educational level in Turkey in 1926, and included an annual 20-day camping exercise. The programme is a little-investigated topic of Turkish education history but is widely considered to have played a key role in shaping social attitudes in the country. This article reports the findings of an analysis of first-hand sources and archive documents relating to the Military Service Preparatory Programme in Turkey between 1926 and 1947 and its lasting effects.
Keywords: Education; militarism; paramilitarism; physical education; Turkish educational system; PHYSICAL-EDUCATION; HISTORY; Education & Educational Research; Social Sciences - Other Topics